Pengabdian Kepada Masyarakat Melalui Pharmacy Care Covid-19 Pemberian Jamu Dan Susu Kurma Untuk Tenaga Kesehatan - Suci Fitriani Sammulia; Suhaera Suhaera; Delladari Mayefis; Sri Hainil; Aria Juanda; Oktasari Oktasari (Jurnal Pengabdian Ilmu Kesehatan, 2021)
Coronavirus Disease 2019 (Covid-19) is a new disease that was first reported in Wuhan, China, and has been recognized as a global pandemic by WHO. The spread of the corona virus occurs through droplets which can be transmitted from person to person, causing problems with the respiratory tract. Meanwhile, milk consumption in Indonesia is still low due to dislike of the smell and taste of milk. One solution to increase milk consumption is through product diversification by adding date juice. Date juice is rich in nutrients and can increase the nutritional value of milk, giving it a sweet taste that people like. Apart from that, the tradition of consuming herbal medicine remains popular in Indonesia as an alternative treatment that is considered safe and does not cause serious side effects. This study aims to evaluate the effect of adding date juice on the organoleptic characteristics of date milk and maintain the sustainability of the use of herbal medicine in Indonesian society.